Concise introduction to basic real analysis - Dutta, Hemen, 1981-; Natarajan, P. N.; Cho, Yeol Je (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book provides an introduction to basic topics in Real Analysis and makes the subject easily understandable to all learners. The book is useful for those that are involved with Real Analysis in disciplines such as mathematics, engineering, technology, and other physical sciences. It provides a good balance while dealing with the basic and essential topics that enable the reader to learn the more advanced topics easily. It includes many examples and end of chapter exercises including hints for solutions in several critical cases. The book is ideal for students, instructors, as well as those doing research in areas requiring a basic knowledge of Real Analysis. Those more advanced in the field will also find the book useful to refresh their knowledge of the topic.
OCLC-licensed vendor bibliographic record.
Keywords: Functions of real variables -- Textbooks; Mathematical analysis -- Textbooks; Numbers, Real -- Textbooks; MATHEMATICS / Applied; MATHEMATICS / Probability & Statistics / General; TECHNOLOGY / Electricity